Microtubules as key coordinators of nuclear envelope and endoplasmic reticulum dynamics during mitosis - Schlaitz, Anne-Lore (Bioessays, 2014)
During mitosis, cells comprehensively restructure their interior to promote the faithful inheritance of DNA and cytoplasmic contents. In metazoans, this restructuring entails disassembly of the nuclear envelope, redistribution of its components into the endoplasmic reticulum (ER) and eventually nuclear envelope reassembly around the segregated chromosomes. The microtubule cytoskeleton has recently emerged as a critical regulator of mitotic nuclear envelope and ER dynamics. Microtubules and associated molecular motors tear open the nuclear envelope in prophase and remove nuclear envelope remnants from chromatin. Additionally, two distinct mechanisms of microtubule-based regulation of ER dynamics operate later in mitosis. First, association of the ER with microtubules is reduced, preventing invasion of ER into the spindle area, and second, organelle membrane is actively cleared from metaphase chromosomes. However, we are only beginning to understand the role of microtubules in shaping and distributing ER and other organelles during mitosis.